Purple Eggplant (Solanum melongena L.) Ameliorates D-Galactose-Induced Cognitive Impairment Through Inhibition of Oxidative Stress and Acetylcholinesterase in the Hippocampus of an Aging Rat Model - Jeefoo, Watcharaporn Preedapirom; Phachonpai, Wathita; Duangjai, Acharaporn; Ontawong, Atcharaporn; Amornlerdpison, Doungporn (Trends in Sciences, 2023)
The induction of neurotoxicity by d-galactose (D-Gal) is a widely recognized model that is utilized for investigating the process of aging and the associated cognitive impairment, as well as oxidative damage and cholinergic dysfunction. Eggplant fruit is a highly consumed vegetable owing to its high phenolic content, which exhibits antioxidant properties. The current investigation aimed to assess the effect of an aqueous extract of Thai purple eggplant (PEP) fruit (Solanum melongena L., ‘Ma Khuea Muang’) on memory impairment and explore the underlying mechanisms. The quantification of total phenolic contents was conducted on the PEP extract, and an analysis of its antioxidant activity was performed using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2-Azino-bis (3-ethyl benzothiazoline-6-sufonic acid) (ABTS) scavenging assays. Male Wistar rats were subcutaneously (s.c.) injected (150 mg/kg/day) with D-Gal to generate a model of accelerated aging and administered orally with EP extract (250, 500, and 1,000 mg/kg/day) or donepezil (DNP) (3 mg/kg/day) for 8 weeks. Cognitive performance was evaluated by the Morris water maze (MWM) and novel object recognition (NOR) tests. Malondialdehyde (MDA) level and acetylcholinesterase (AChE) and superoxide dismutase (SOD) activities in the hippocampus were also evaluated after the behavioral studies. The continuous administration of PEP extract at a dosage of 1,000 mg/kg/day or DNP resulted in the amelioration of cognitive impairment and the reversal of the increase in AChE activity caused by D-Gal in the hippocampus. Furthermore, the administration of PEP extract resulted in a significant reduction in MDA levels in the hippocampus. These findings suggest a potential attenuation of oxidative stress. The findings indicate that the PEP extract has a beneficial effect on cognitive decline induced by D-Gal, which is attributed to the restoration of cholinergic function and the reduction of oxidative damage. HIGHLIGHTS In D-galactose-induced aged rats, purple eggplant (Solanum melongena) (PEP) extract can inhibit elevated acetylcholinesterase (AChE) activity and malondialdehyde (MDA) levels in the hippocampus. The consumption of PEP extract has been found to have potential benefits in improving age-related learning and memory impairment. The utilization of PEP extract as a dietary supplement may serve as a viable option for the elderly population in the prevention of dementia. GRAPHICAL ABSTRACT